2015
DOI: 10.1002/imhj.21540
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the 20-Week Circle of Security Intervention: Changes in Caregiver Reflective Functioning, Representations, and Child Attachment in an Australian Clinical Sample

Abstract: Circle of Security is an attachment theory based intervention that aims to promote secure parent-child attachment relationships. Despite extensive uptake of the approach, there is limited empirical evidence regarding efficacy. The current study examined whether participation in the 20-week Circle of Security intervention resulted in positive caregiver-child relationship change in four domains: caregiver reflective functioning; caregiver representations of the child and the relationship with the child; child at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 40 publications
2
58
0
1
Order By: Relevance
“…In two studies, the original COS 20-week protocol was associated with significant decreases in attachment insecurity and disorganization, as compared to attachment assessed prior to COS (Hoffman et al, 2006; Huber, McMahon, & Sweller, 2015a). Further, in a RCT, a four-session home-visiting version of the COS video-feedback protocol revealed interaction effects among intervention, infant temperament, and maternal attachment style; a key finding was that the COS intervention was efficacious in reducing insecure attachment for infant–mother dyads at greatest risk (Cassidy, Woodhouse, Sherman, Stupica, & Lejuez, 2011).…”
Section: The Circle Of Security–parenting (Cos-p) Interventionmentioning
confidence: 99%
“…In two studies, the original COS 20-week protocol was associated with significant decreases in attachment insecurity and disorganization, as compared to attachment assessed prior to COS (Hoffman et al, 2006; Huber, McMahon, & Sweller, 2015a). Further, in a RCT, a four-session home-visiting version of the COS video-feedback protocol revealed interaction effects among intervention, infant temperament, and maternal attachment style; a key finding was that the COS intervention was efficacious in reducing insecure attachment for infant–mother dyads at greatest risk (Cassidy, Woodhouse, Sherman, Stupica, & Lejuez, 2011).…”
Section: The Circle Of Security–parenting (Cos-p) Interventionmentioning
confidence: 99%
“…Reduced child behavior problems (Huber et al 2015a), may also have contributed to reduced parenting stress, as our exploratory analyses indicated associations between these changes. There are robust links between child behavioral and emotional functioning and parent emotional functioning because of the transactional nature of the parent-child relationship (e.g.…”
Section: Change In Parenting Stress By Baseline Severity Groupmentioning
confidence: 94%
“…A subsequent study with the same sample found improved child behavioral and emotional adjustment after the Circle of Security intervention, including parent reported increases in child social and emotional protective factors, parent reported reductions in child behavioral concerns and internalizing symptoms, and parent and teacher reported decreases in child externalizing symptoms, all with medium effect sizes (Huber et al 2015a). The current study aimed to extend these findings by examining whether participating in the Circle of Security 20-week intervention was also associated with reduced parenting stress and psychological symptomatology.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Research with infants and young children has shown that parents who attribute their child’s misbehavior to internal, stable characteristics are more likely to use harsh and overreactive parenting practices (Snarr et al, 2009). Similarly, mothers with more negative caregiving schemas were found to be less sensitive, less engaged, and less encouraging in parent-child interactions, (Huber, McMahon, & Sweller, 2015; Slade, Belsky, Aber, & Phelps, 1999). However, despite the well-established findings with parents of young children, when it comes to adolescence, only one study has tested for a direct link between parental caregiving representations and parenting behavior.…”
Section: Caregiving Representations As Determinants Of Parentingmentioning
confidence: 99%